The Peruvian cultural heritage as the path to economic and social development and national defense Its fragility to changes and innovation of the neo-modernity - De Orellana Rojas, Juan E. (2012)
This study postulates that nowadays there are two specially marked currents for the development such as "neo-modernity"and "hypermodernity". It is considered that the first one has its clearest expression in the so-called Neoliberalism which is acontinuation or the rattles of the exploitative and capitalist industrial world. Furthermore, it is believed that actually is amercantilist liberalism because it lives on "lobbies" and approaches or "productive flirtations" of the economic power withthe political power (and even religious). The second one come out from a conception of the world, the man, his society andculture and plural, which can coexist, live together and be respect, and that part of the "ideological corpse" of thepostmodernism and its postulates. It is not intended to be a communist socialism, but an equal opportunities for all and anequality of remuneration for the work. In this framework, it develops a study on the endangered non-Western heritage (eventhe western, but to a lesser extent) to succeed the first current mentioned previously ; it would be a world without memory andwhose future will remain the exploitation with other masks and the depressive, demotivating and boring mega-consumerism,without identity or civic and national consciousness.